Everything is a lie: rape culture, rape myths and false beliefs about sexual violence against women - Tardón Recio, Bárbara (Política y Sociedad, 2022)
This article addresses the significance of rape and other forms of sexual violence, understood as devices for control of women’s autonomy and sexual freedom. With the aim of combating sexual violence, this document analyzed the elements that sustain and justify all types of sexual violence: patriarchal ideology, rape culture, rape myths and consent.